Inventarisasi dan Komposisi Jenis Ektoparasit Ikan Nila (Oreochromis niloticus) Sebagai Biomonitoring Perairan Sungai Tukad Badung, Bali - Alfi Hermawati Waskita Sari; Rani Ekawaty (Journal of Marine and Aquatic Sciences, 2019)
Environmental stressors which coming from anthropogenic wastes that indirectly enters into the river waters also affect the biota's health in the ecosystem such as the Tilapia Fish (Oreochromis niloticus) which is found in the waters of the Tukad Badung River, Bali. The presence of parasites in fish is also associated with changes of the water quality. The objectives of this study is to provide data and information on the inventory and composition of the parasite species in Tilapia fish (Oreochromis niloticus) as the aquatic health biomonitoring of in the effort of sustainable river ecosystem management. The results of ectoparasit observation of the Tilapia which obtained from five stations in Tukad Badung waters found 6 types of ectoparasites, which are Trichodina sp. Dactylogyrus sp. Gyrodactylus sp., Chilodonella sp., Vorticella sp. and Lernea sp. The composition of the ectoparasite species of nila tilapia fish (Oreochromis niloticus) obtained from all five research stations in Tukad Badung waters by percentage of presence of ectoparasite Trichodina sp. are 70%, Dactylogyrus sp. 31%, Gyrodactylus sp. 4% and Chilodonella sp., Vorticella sp. and Lernea sp. 1%.